Aspergillus Bibliography - John Clutterbuck (Fungal Genetics Reports, 2005)
This bibliography attempts to cover genetical and biochemical publications on Aspergillus nidulans and also includes selected references to related species and topics. Entries have been checked as far as possible, but please tell me of any errors and omissions. Authors are kindly requested to send a copy of each article to the FGSC for its reprint collection.